Normative adductor squeeze test values in elite junior rugby union players - Coughlan, G. F.; Delahunt, E.; Caulfield, B. M.; Forde, C.; Green, B. S. (Clinical Journal of Sport Medicine, 2014)
Objective: To establish normative adductor squeeze test (AST) values in elite junior rugby union players and investigate if differences existed between field position units and categorizations.